Analisis Kinerja Keuangan Bank Syariah dan Bank Konvensional di Masa Pandemi Covid-19 Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Devi Afikasari; Achmad Maqsudi (Pusat Riset dan Inovasi Nasional, 2023)
The author conducted this research at PT Bank Rakyat Indonesia Tbk which is listed on the Indonesia Stock Exchange (IDX), PT Bank Central Asia Tbk, PT Bank Syariah Indonesia Tbk, and PT Bank BTPN Syariah Tbk. Risk Profile, Earnings, and Capital (RGEC), and Good Corporate Governance (GCG) are the methods used for this research. This study aims to determine the financial performance of Islamic and conventional banks during the Covid-19 pandemic in terms of risk profile, good corporate governance (GCG), profitability, and capital. This type of research is quantitative, the type of data used is secondary data, the data collection technique used was documentation technique and the data analysis method was a quantitative descriptive method. The results showed that the financial performance of PT Bank Rakyat Indonesia Tbk was in good condition, PT Bank Central Asia Tbk was in very good condition, PT Bank Syariah Indonesia Tbk was in very good condition PT Bank BTPN Syariah Tbk good condition.